Screening and Early Diagnosis of Hepatocellular Cancer and Optimization of Diagnostic Imaging Techniques: A Review and Conclusion of the Expert Panel - V. V. Breder; R. B. Alikhanov; S. S. Bagnenko; E. N. Bessonova; V. A. Isakov; N. E. Kudashkin; B. M. Medvedeva; A. V. Mishchenko; M. S. Novruzbekov; V. S. Rudakov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Аim: to describe modern approaches for screening and early diagnosis of hepatocellular carcinoma (HCC).Key points. Screening for HCC in high-risk groups (cirrhosis of any etiology, patients with chronic viral hepatitis B and patients with F3 liver fibrosis) should be organized as regular (every 6 months) liver ultrasound in combination with determination of the serum alpha-fetoprotein (AFP) level. At an AFP level of ≥ 20 ng/ml, even in the absence of changes according to ultrasound data, it is advisable to perform MRI with a hepatospecific contrast agent (gadoxetic acid) which makes it possible to detect very small focal liver lesions. If focal liver lesions of 1–2 cm are detected on ultrasound, additional imaging of the liver using MRI with a hepatospecific contrast agent gadoxetic acid helps to identify HCC at an earlier stage or high degree dysplastic nodes. When planning surgical treatment and liver transplantation, it is preferable to use MRI with a hepatospecific contrast agent, since the presence of the hepatobiliary phase may allow the detection of additional smaller focal liver lesions and assess the nature of the focal liver lesion. When a patient is included in the waiting list for liver transplantation, the optimal frequency of liver MRI is 1 time in 3 months.Conclusion. MRI with hepatospecific contrast agent gadoxetic acid is effective in screening, early diagnosis and treatment planning for HCC.